Strategic Planning Model for Halal Tourism: Gravity Adventure Pangalengan Case Study - Silmi Millatina Wahdini (Research Synergy Foundation, 2025)
Gravity Adventure is one of the pioneers in the nature adventure industry in South Bandung, especially in the field of rafting and other outdoor adventure activities. This study aims to analyze the planning, implementation, and evaluation strategies for realizing halal tourism at Gravity Adventure, a nature-based destination in Pangalengan, Bandung Regency. Using a qualitative descriptive method, data were collected through interviews, observations, and document studies. Findings reveal that although Gravity Adventure has not yet received formal halal certification, it has integrated key halal elements, such as prayer facilities and halal food offerings, based on local religious values. The strategic approach integrates SWOT analysis and a modified Business Model Canvas (BMC), both of which are adapted to align with Islamic principles. The study contributes a contextual framework for the sustainable development of halal tourism in nature-based community destinations, suggesting strategies such as digital promotion, stakeholder collaboration, and service innovation target Muslim travelers.